Poultry Manure with Inorganic Nitrogen on Growth and Yield of Onion (Allium cepa L.) - Mia, MA Baset; Akter, Sanjida; Molla, AH; Rahman, GKM Mustafizur (The Agriculturists, 2010)
An experiment was conducted at the research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) in 2004 to investigate the effect of poultry manure along with inorganic N-fertilizer on the nutrient uptake, growth and yield of onion. The onion (Allium cepa L.) cv. Taherpuri was grown under six treatments viz. recommended dose of inorganic N (115 kg ha-1, 100% N), 75% of inorganic N + 5 t ha-1 poultry manure, 50% inorganic N + 10 t ha-1 poultry manure, 25% inorganic N + 15 t ha-1 poultry manure, 15 t ha-1 poultry manure and absolute control (without poultry manure and inorganic N). Plant height, total dry matter, single bulb weight, yield and nutrients uptake at different growth stages of onion varied significantly due to application of poultry manure and inorganic- N fertilizer. Among the treatments, the highest yield (10.1t ha-1) and yield attributes of onion were recorded under the application of 50% inorganic N with 10 t ha-1 of poultry manure, which was 14% higher compared to 100% inorganic-N fertilizer. The higher nutrient uptake viz. N, P and K was noted in plot where poultry manure was applied at 10 t ha-1 along with 50% inorganic-N. It is concluded that application of 10 t ha-1 poultry manure was enough to reduce 50% inorganic-N in onion cultivation.